EFFECTS OF GAP YEAR ON CAREER TRANSITIONS: A QUALITATIVE STUDY - Erdogmus, Nihat; Mirzanli, Dogus (PRESSACADEMIA, 2016)
It is asserted that gap year activities have positive contributions, such as analyzing the current situation, evaluating potential transition scenarios, and gaining new abilities that facilitate career transition, to the qualified workforce that decided to change their career paths due to job related dissatisfaction with a sound and accurate implementations. In this study, volunteers that took a break to their professional lifes and worked abroad for Non Profit Organisations due to personal or professional dissatisfaction while working in the area that was related to their academic education were examined. Also reasons of gap year, causes and incentives of career transition, benefits acquired in the gap year and career transition after the process were investigated. Sample group was selected from the professionals that joined the European Volunteer Service projects 4 to 12 months. In data collection process semi structured interviews were held with the sample group of 17 people who are selected in accordance with the predetermined criteria. The results showed that gap year has positive contibutions on career transitions.
Keywords: Gap year; volunteering; non-profit organisations; career transition; MODEL; WORK; Business & Economics